Corundum crucible and preparation method thereof

Through specific formula ratio and grouting method molding processes, the existing alumina crucible preparation process is solved, and the high strength, low-fire shrinkage corundum crucible is achieved, which improves yield and production efficiency.

CN119797942APending Publication Date: 2025-04-11HUNAN DJY-TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411932519.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-26
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

The existing alumina crucible preparation process is complex, the wax discharge process has a large environmentally friendly processing pressure, high calcining temperature, high energy consumption, and low yield, making it difficult to achieve large-scale mass production.

Method used

The specific formula ratio and grouting method are used to uniformly suspend the calcined alumina fine powder through ball milling, and the gypsum mold is injected into molding, controlling the wall thickness and composition are evenly dispersed, reducing the sintering temperature, and improving the strength and density of the crucible.

Benefits of technology

It has achieved high-strength, low-fire shrinkage, and low porosity corundum crucibles, shortened production cycle, improved yield, reduced energy consumption, and had wide application prospects.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005210707120000111
    Figure BDA0005210707120000111
Patent Text Reader

Abstract

The invention discloses a corundum crucible and a preparation method thereof, and belongs to the technical field of crucibles, the corundum crucible comprises the following preparation raw materials by weight: 95-99 parts of alumina, 1-5 parts of calcium carbonate, 1-5 parts of dolomite, 1-5 parts of kaolin, 1-5 parts of zirconia, 1-5 parts of zirconium silicate, 1-5 parts of zirconite, 1-5 parts of silica powder, 1-5 parts of quartz powder, 1-5 parts of yttrium oxide, 1-5 parts of lanthanum oxide, and 2-10 parts of an auxiliary agent. The raw materials are combined to obtain the corundum crucible which is high in density, uniform, high in strength, small in sintering shrinkage deformation, accurate in size and high in yield, and the corundum crucible is short in long body period and has wide application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of crucibles, and in particular to a corundum crucible and a preparation method thereof. Background Art

[0002] Corundum crucible, scientific name alumina crucible, is a crucible made of calcined alumina powder (α crystal form). Corundum crucible has high strength, extremely low porosity and water absorption, excellent corrosion resistance and will not pollute the melt. It is a non-toxic, harmless, environmentally friendly high-temperature resistant material. Therefore, it is mainly used in high-temperature smelting, experimental analysis and chemical reactions.

[0003] In the preparation of existing alumina crucibles, paraffin wax is often required as a binder, followed by a wax removal process, which is relatively complicated. The environmental protection treatment pressure of the wax removal process is relatively high, and the subsequent calcination temperature is relatively high, basically between 1500 and 1700°C, which has high requirements for the calcination kiln and consumes a lot of energy.

[0004] The traditional slip injection molding method for preparing alumina crucibles has low green body strength, large shrinkage during drying and firing, and low yield. The slip injection method also requires a large number of plaster molds, which is labor-intensive, low in production efficiency, and has a long production cycle, making it difficult to mass produce on a large scale.

[0005] In view of this, this application is filed. Summary of the invention

[0006] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a corundum crucible and a preparation method thereof. The corundum crucible has high strength and a reduced sintering yield and has broad application prospects.

[0007] To achieve the above object, the technical solution adopted by the present invention is:

[0008] A corundum crucible comprises the following raw materials in parts by weight: 95-99 parts of aluminum oxide, 1-5 parts of calcium carbonate, 1-5 parts of dolomite, 1-5 parts of kaolin, 1-5 parts of zirconium oxide, 1-5 parts of zirconium silicate, 1-5 parts of zircon, 1-5 parts of silicon micropowder, 1-5 parts of quartz powder, 1-5 parts of yttrium oxide, 1-5 parts of lanthanum oxide, and 2-10 parts of additives.

[0009] The present invention creatively combines the above raw materials to obtain a corundum crucible with high density, uniformity, high strength, small sintering shrinkage deformation, accurate size and high yield rate. The corundum crucible has a short growth period and has broad application prospects.

[0010] The manufacturing method of the corundum ceramic crucible of the present invention is to form by slip injection method, wherein calcined alpha alumina, calcium carbonate, dolomite, kaolin, zirconium oxide, zirconium silicate, zircon, silicon micropowder, quartz powder, yttrium oxide, lanthanum oxide, additives and appropriate amount of water are ball-milled in a ball mill, so that the calcined alumina fine powder is uniformly suspended in a solution to form slurry, which is then injected into a gypsum mold. After a certain period of time, the slurry is adsorbed on the wall of the gypsum mold, and the length of the adsorption time determines the wall thickness of the crucible. When the thickness requirement is reached, the slurry not adsorbed in the gypsum mold is discharged, and a layer of slurry adsorbed on the wall of the gypsum mold and solidified is left in the gypsum mold. After drying, the slurry is demoulded to form a crucible blank. After the blank is dried under appropriate conditions, it is sintered at high temperature to obtain the corundum crucible.

[0011] By adopting the specific formula and proportion of the present invention in combination with the specific grouting method for molding, the wall thickness of the crucible can be accurately regulated, the dimensional uniformity can be improved, the uneven wall thickness or defects that may be caused by other molding methods can be avoided, the uniform dispersion of the components can be promoted, the strength of the crucible can be improved, the shrinkage rate can be reduced, the porosity can be reduced, the compactness can be improved, the thermal shock resistance of the crucible can be improved, and cracks or breakages are not easily generated. The addition of modifiers (calcium carbonate, dolomite, kaolin, zirconium oxide, zirconium silicate, zircon, silicon powder, quartz powder, yttrium oxide, and lanthanum oxide are collectively referred to as modifiers) can reduce the sintering temperature, improve the strength of the corundum crucible, and more effectively improve the shrinkage rate of the crucible.

[0012] As a preferred embodiment of the present invention, the alumina comprises a first calcined α-alumina and a second calcined α-alumina; the mass ratio of the first calcined α-alumina and the second calcined α-alumina is 1:(0.5-2);

[0013] The first calcined α-alumina is obtained by calcining α-alumina at 1250-1280° C.

[0014] The second calcined α-alumina is obtained by calcining α-alumina at 1420-1450°C.

[0015] As a preferred embodiment of the present invention, the average particle size of the first calcined α-alumina is 0.5-1 μm; the average particle size of the second calcined α-alumina is 2-4 μm.

[0016] As a preferred embodiment of the present invention, the particle size of the calcium carbonate is ≥1000 mesh;

[0017] The particle size of the dolomite is ≥1000 mesh;

[0018] The particle size of the kaolin is ≥1000 mesh;

[0019] The particle size of the zirconium silicate is ≥1000 mesh;

[0020] The particle size of the zircon is ≤800 mesh.

[0021] As a preferred embodiment of the present invention, the particle size of the calcium carbonate is 1000-2000 mesh;

[0022] The particle size of the dolomite is 1000-2000 mesh;

[0023] The particle size of the kaolin is 1000-2000 mesh;

[0024] The particle size of the zirconium silicate is 1000-2000 mesh;

[0025] The particle size of the zircon is 400-800 meshes.

[0026] As a preferred embodiment of the present invention, the average particle size of the zirconium oxide is ≤5 μm;

[0027] The average particle size of the silicon powder is ≤5 μm;

[0028] The average particle size of the quartz powder is ≤5 μm;

[0029] The average particle size of the lanthanum oxide is ≤5 μm.

[0030] As a preferred embodiment of the present invention, the average particle size of the zirconium oxide is 1 to 5 μm;

[0031] The average particle size of the silicon powder is 1 to 5 μm;

[0032] The average particle size of the quartz powder is 1 to 5 μm;

[0033] The average particle size of the lanthanum oxide is 1 to 5 μm.

[0034] As a preferred embodiment of the present invention, the auxiliary agent includes at least one of ammonium polyacrylate, polyvinyl alcohol and polyvinyl pyrrolidone.

[0035] The present invention also provides a method for preparing a corundum crucible, comprising the following steps:

[0036] Weigh the raw materials according to the proportion, mix them evenly, add water to prepare a slurry with a solid content of 55-65wt%; ball mill until the D90 of the slurry is ≤8μm;

[0037] The slurry is placed in a gypsum mold, and the gypsum mold is allowed to absorb the slurry; after the adsorption thickness of the gypsum mold reaches a target value, it is dried and sintered to obtain a corundum crucible.

[0038] As a preferred embodiment of the present invention, the sintering is specifically:

[0039] First, heat up to 880-920°C at a rate of 2.5-3°C / min, then heat up to 1450-1550°C at a rate of 1-2°C / min, then keep at 1450-1550°C for 2-5h, then cool down to 880-920°C at a rate of 2.5-3°C / min, then cool down to 280-320°C at a rate of 1-2°C / min, and finally cool naturally to room temperature.

[0040] The beneficial effects of the present invention are as follows: (1) The method for making a corundum ceramic crucible of the present invention is to form a crucible by a slip injection method, wherein calcined α-alumina, calcium carbonate, dolomite, kaolin, zirconium oxide, zirconium silicate, zircon, silicon powder, quartz powder, yttrium oxide, lanthanum oxide, additives and an appropriate amount of water are ball-milled in a ball mill to uniformly suspend the calcined alumina fine powder in a solution to form a slurry, which is then injected into a gypsum mold. After a certain period of time, the slurry is adsorbed on the wall of the gypsum mold. The length of the adsorption time determines the wall thickness of the crucible. When the required thickness is reached, the slurry that has not been adsorbed in the gypsum mold is discharged, and a layer of slurry that is adsorbed on the wall of the gypsum mold and solidified remains in the gypsum mold. After drying, the crucible is demolded to form a crucible blank. After the blank is dried under appropriate conditions, it is sintered at a high temperature to obtain a corundum crucible.

[0041] (2) The specific formula and ratio of the present invention are combined with a specific slurry injection molding method to accurately control the wall thickness of the crucible, improve the dimensional uniformity, avoid the uneven wall thickness or defects that may be caused by other molding methods, promote the uniform dispersion of the various components, improve the strength of the crucible and reduce the shrinkage rate, reduce the porosity, improve the density, improve the thermal shock resistance of the crucible, and make it less likely to crack or break. The addition of modifiers (calcium carbonate, dolomite, kaolin, zirconium oxide, zirconium silicate, zircon, silicon powder, quartz powder, yttrium oxide, and lanthanum oxide are collectively referred to as modifiers) reduces the sintering temperature, improves the strength of the corundum crucible, and more effectively improves the shrinkage rate of the crucible. DETAILED DESCRIPTION

[0042] In order to make the purpose, technical solutions and advantages of the embodiments of the present application clearer, the technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present application, not all of the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present application.

[0043] In the present application, the technical features described in an open manner include closed technical solutions composed of the listed features, and also include open technical solutions containing the listed features.

[0044] In this application, when it comes to numerical ranges, unless otherwise specified, the above numerical ranges are deemed to be continuous and include the minimum and maximum values ​​of the range, as well as each value between such minimum and maximum values. Further, when a range refers to an integer, each integer between the minimum and maximum values ​​of the range is included. In addition, when multiple ranges are provided to describe features or characteristics, the ranges can be merged. In other words, unless otherwise specified, all ranges disclosed herein should be understood to include any and all subranges included therein.

[0045] In the present application, there is no particular limitation on the specific dispersion and stirring treatment methods.

[0046] Unless otherwise specified, the components, raw materials or instruments used in the embodiments and comparative examples of the present invention are all commercially available raw materials or instruments, and the components and raw materials used in each parallel experiment are all of the same kind.

[0047] In addition, the terms "first" and "second" are used for descriptive purposes only and should not be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.

[0048] The following examples are provided to facilitate understanding of the present invention. These examples are not provided to limit the scope of the claims.

[0049] Example 1

[0050] A corundum crucible comprises the following raw materials in parts by weight: 95 parts of aluminum oxide, 5 parts of calcium carbonate, 1 part of dolomite, 5 parts of kaolin, 1 part of zirconium oxide, 5 parts of zirconium silicate, 1 part of zircon, 5 parts of silicon micropowder, 1 part of quartz powder, 5 parts of yttrium oxide, 1 part of lanthanum oxide, 5 parts of polyvinyl pyrrolidone (K90), and 5 parts of polyvinyl alcohol (PVA1000).

[0051] The alumina includes a first calcined α-alumina and a second calcined α-alumina; the mass ratio of the first calcined α-alumina to the second calcined α-alumina is 1:1;

[0052] The preparation method of the first calcined α-alumina is: calcining the α-alumina at 1260° C. for 4 hours and grinding it to an average particle size of 1 μm.

[0053] The second calcined α-alumina preparation method is: calcining the α-alumina at 1450° C. for 4 hours, and grinding the α-alumina to an average particle size of 2 μm.

[0054] The particle size of the calcium carbonate is 2000 mesh; the particle size of the dolomite is 2000 mesh; the particle size of the kaolin is 2000 mesh; the particle size of the zirconium silicate is 2000 mesh; and the particle size of the zircon is 800 mesh.

[0055] The average particle size of the zirconium oxide is 4 μm; the average particle size of the silicon powder is 4 μm; the average particle size of the quartz powder is 4 μm; and the average particle size of the lanthanum oxide is 4 μm.

[0056] The method for preparing the corundum crucible comprises the following steps:

[0057] Weigh the raw materials according to the proportion, mix them evenly, add water to prepare a slurry with a solid content of 60t%; ball mill until the D90 of the slurry is ≤8μm;

[0058] The slurry is placed in a gypsum mold, and the gypsum mold is allowed to absorb the slurry; when the gypsum mold adsorption thickness reaches 6mm, it is placed in a cool place to dry, and after the green body evaporates with the water, the green body is separated from the gypsum mold and sintered to obtain a corundum crucible. The sintering is specifically as follows: firstly, the temperature is raised to 900°C at a rate of 3°C / min, then the temperature is raised to 1480°C at a rate of 2°C / min, then the temperature is kept at 1480°C for 3h, then the temperature is lowered to 900°C at a rate of 3°C / min, then the temperature is lowered to 300°C at a rate of 2°C / min, and finally the crucible is naturally cooled to room temperature.

[0059] Example 2

[0060] A corundum crucible comprises the following raw materials in parts by weight: 99 parts of aluminum oxide, 1 part of calcium carbonate, 5 parts of dolomite, 1 part of kaolin, 5 parts of zirconium oxide, 1 part of zirconium silicate, 5 parts of zircon, 1 part of silicon micropowder, 5 parts of quartz powder, 1 part of yttrium oxide, 5 parts of lanthanum oxide, 1 part of polyvinyl pyrrolidone (K90), and 1 part of polyvinyl alcohol (PVA1000).

[0061] The alumina includes a first calcined α-alumina and a second calcined α-alumina; the mass ratio of the first calcined α-alumina to the second calcined α-alumina is 1:1;

[0062] The preparation method of the first calcined α-alumina is: calcining the α-alumina at 1260° C. for 4 hours and grinding it to an average particle size of 1 μm.

[0063] The second calcined α-alumina preparation method is: calcining the α-alumina at 1450° C. for 4 hours, and grinding the α-alumina to an average particle size of 2 μm.

[0064] The particle size of the calcium carbonate is 2000 mesh; the particle size of the dolomite is 2000 mesh; the particle size of the kaolin is 2000 mesh; the particle size of the zirconium silicate is 2000 mesh; and the particle size of the zircon is 800 mesh.

[0065] The average particle size of the zirconium oxide is 4 μm; the average particle size of the silicon powder is 4 μm; the average particle size of the quartz powder is 4 μm; and the average particle size of the lanthanum oxide is 4 μm.

[0066] The method for preparing the corundum crucible comprises the following steps:

[0067] Weigh the raw materials according to the proportion, mix them evenly, add water to prepare a slurry with a solid content of 60t%; ball mill until the D90 of the slurry is ≤8μm;

[0068] The slurry is placed in a gypsum mold, and the gypsum mold is allowed to absorb the slurry; when the gypsum mold adsorption thickness reaches 6mm, it is placed in a cool place to dry, and after the green body evaporates with the water, the green body is separated from the gypsum mold and sintered to obtain a corundum crucible. The sintering is specifically as follows: firstly, the temperature is raised to 900°C at a rate of 3°C / min, then the temperature is raised to 1480°C at a rate of 2°C / min, then the temperature is kept at 1480°C for 3h, then the temperature is lowered to 900°C at a rate of 3°C / min, then the temperature is lowered to 300°C at a rate of 2°C / min, and finally the crucible is naturally cooled to room temperature.

[0069] Example 3

[0070] A corundum crucible comprises the following raw materials in parts by weight: 95 parts of aluminum oxide, 5 parts of calcium carbonate, 1 part of dolomite, 5 parts of kaolin, 1 part of zirconium oxide, 5 parts of zirconium silicate, 1 part of zircon, 5 parts of silicon micropowder, 1 part of quartz powder, 5 parts of yttrium oxide, 1 part of lanthanum oxide, 5 parts of polyvinyl pyrrolidone (K90), and 5 parts of polyvinyl alcohol (PVA1000).

[0071] The alumina includes a first calcined α-alumina and a second calcined α-alumina; the mass ratio of the first calcined α-alumina to the second calcined α-alumina is 1:0.5.

[0072] The preparation method of the first calcined α-alumina is: calcining the α-alumina at 1260° C. for 4 hours and grinding it to an average particle size of 1 μm.

[0073] The second calcined α-alumina preparation method is: calcining the α-alumina at 1450° C. for 4 hours, and grinding the α-alumina to an average particle size of 2 μm.

[0074] The particle size of the calcium carbonate is 2000 mesh; the particle size of the dolomite is 2000 mesh; the particle size of the kaolin is 2000 mesh; the particle size of the zirconium silicate is 2000 mesh; and the particle size of the zircon is 800 mesh.

[0075] The average particle size of the zirconium oxide is 4 μm; the average particle size of the silicon powder is 4 μm; the average particle size of the quartz powder is 4 μm; and the average particle size of the lanthanum oxide is 4 μm.

[0076] The method for preparing the corundum crucible comprises the following steps:

[0077] Weigh the raw materials according to the proportion, mix them evenly, add water to prepare a slurry with a solid content of 60t%; ball mill until the D90 of the slurry is ≤8μm;

[0078] The slurry is placed in a gypsum mold, and the gypsum mold is allowed to absorb the slurry; when the gypsum mold adsorption thickness reaches 6mm, it is placed in a cool place to dry, and after the green body evaporates with the water, the green body is separated from the gypsum mold and sintered to obtain a corundum crucible. The sintering is specifically as follows: firstly, the temperature is raised to 900°C at a rate of 3°C / min, then the temperature is raised to 1480°C at a rate of 2°C / min, then the temperature is kept at 1480°C for 3h, then the temperature is lowered to 900°C at a rate of 3°C / min, then the temperature is lowered to 300°C at a rate of 2°C / min, and finally the crucible is naturally cooled to room temperature.

[0079] Example 4

[0080] A corundum crucible comprises the following raw materials in parts by weight: 95 parts of aluminum oxide, 5 parts of calcium carbonate, 1 part of dolomite, 5 parts of kaolin, 1 part of zirconium oxide, 5 parts of zirconium silicate, 1 part of zircon, 5 parts of silicon micropowder, 1 part of quartz powder, 5 parts of yttrium oxide, 1 part of lanthanum oxide, 5 parts of polyvinyl pyrrolidone (K90), and 5 parts of polyvinyl alcohol (PVA1000).

[0081] The alumina includes a first calcined α-alumina and a second calcined α-alumina; the mass ratio of the first calcined α-alumina to the second calcined α-alumina is 1:2.

[0082] The preparation method of the first calcined α-alumina is: calcining the α-alumina at 1260° C. for 4 hours and grinding it to an average particle size of 1 μm.

[0083] The second calcined α-alumina preparation method is: calcining the α-alumina at 1450° C. for 4 hours and grinding it to an average particle size of 2 μm.

[0084] The particle size of the calcium carbonate is 2000 mesh; the particle size of the dolomite is 2000 mesh; the particle size of the kaolin is 2000 mesh; the particle size of the zirconium silicate is 2000 mesh; and the particle size of the zircon is 800 mesh.

[0085] The average particle size of the zirconium oxide is 4 μm; the average particle size of the silicon powder is 4 μm; the average particle size of the quartz powder is 4 μm; and the average particle size of the lanthanum oxide is 4 μm.

[0086] The method for preparing the corundum crucible comprises the following steps:

[0087] Weigh the raw materials according to the proportion, mix them evenly, add water to prepare a slurry with a solid content of 60t%; ball mill until the D90 of the slurry is ≤8μm;

[0088] The slurry is placed in a gypsum mold, and the gypsum mold is allowed to absorb the slurry; when the gypsum mold adsorption thickness reaches 6mm, it is placed in a cool place to dry, and after the green body evaporates with the water, the green body is separated from the gypsum mold and sintered to obtain a corundum crucible. The sintering is specifically as follows: firstly, the temperature is raised to 900°C at a rate of 3°C / min, then the temperature is raised to 1480°C at a rate of 2°C / min, then the temperature is kept at 1480°C for 3h, then the temperature is lowered to 900°C at a rate of 3°C / min, then the temperature is lowered to 300°C at a rate of 2°C / min, and finally the crucible is naturally cooled to room temperature.

[0089] Example 5

[0090] A corundum crucible comprises the following raw materials in parts by weight: 95 parts of aluminum oxide, 5 parts of calcium carbonate, 1 part of dolomite, 5 parts of kaolin, 1 part of zirconium oxide, 5 parts of zirconium silicate, 1 part of zircon, 5 parts of silicon micropowder, 1 part of quartz powder, 5 parts of yttrium oxide, 1 part of lanthanum oxide, 5 parts of polyvinyl pyrrolidone (K90), and 5 parts of polyvinyl alcohol (PVA1000).

[0091] The alumina includes a first calcined α-alumina and a second calcined α-alumina; the mass ratio of the first calcined α-alumina to the second calcined α-alumina is 1:1;

[0092] The preparation method of the first calcined α-alumina is: calcining the α-alumina at 1260° C. for 4 hours and grinding it to an average particle size of 0.5 μm.

[0093] The second calcined α-alumina preparation method is: calcining the α-alumina at 1450° C. for 4 hours, and grinding the α-alumina to an average particle size of 4 μm.

[0094] The particle size of the calcium carbonate is 2000 mesh; the particle size of the dolomite is 2000 mesh; the particle size of the kaolin is 2000 mesh; the particle size of the zirconium silicate is 2000 mesh; and the particle size of the zircon is 800 mesh.

[0095] The average particle size of the zirconium oxide is 4 μm; the average particle size of the silicon powder is 4 μm; the average particle size of the quartz powder is 4 μm; and the average particle size of the lanthanum oxide is 4 μm.

[0096] The method for preparing the corundum crucible comprises the following steps:

[0097] Weigh the raw materials according to the proportion, mix them evenly, add water to prepare a slurry with a solid content of 60t%; ball mill until the D90 of the slurry is ≤8μm;

[0098] The slurry is placed in a gypsum mold, and the gypsum mold is allowed to absorb the slurry; when the gypsum mold adsorption thickness reaches 6mm, it is placed in a cool place to dry, and after the green body evaporates with the water, the green body is separated from the gypsum mold and sintered to obtain a corundum crucible. The sintering is specifically as follows: firstly, the temperature is raised to 900°C at a rate of 3°C / min, then the temperature is raised to 1480°C at a rate of 2°C / min, then the temperature is kept at 1480°C for 3h, then the temperature is lowered to 900°C at a rate of 3°C / min, then the temperature is lowered to 300°C at a rate of 2°C / min, and finally the crucible is naturally cooled to room temperature.

[0099] Comparative Example 1

[0100] The difference between Comparative Example 1 and Example 1 is that the amount of each raw material is different, and the others are the same.

[0101] A corundum crucible comprises the following raw materials in parts by weight: 80 parts of aluminum oxide, 8 parts of calcium carbonate, 0.5 parts of dolomite, 8 parts of kaolin, 0.5 parts of zirconium oxide, 8 parts of zirconium silicate, 0.5 parts of zircon, 8 parts of silicon micropowder, 0.5 parts of quartz powder, 8 parts of yttrium oxide, 0.5 parts of lanthanum oxide, 5 parts of polyvinyl pyrrolidone (K90), and 5 parts of polyvinyl alcohol (PVA1000).

[0102] Comparative Example 2

[0103] The difference between Comparative Example 2 and Example 1 is that the amount of each raw material is different, and the others are the same.

[0104] A corundum crucible comprises the following raw materials in parts by weight: 120 parts of aluminum oxide, 0.5 parts of calcium carbonate, 8 parts of dolomite, 0.5 parts of kaolin, 8 parts of zirconium oxide, 0.8 parts of zirconium silicate, 8 parts of zircon, 0.5 parts of silicon micropowder, 8 parts of quartz powder, 0.5 parts of yttrium oxide, 8 parts of lanthanum oxide, 5 parts of polyvinyl pyrrolidone (K90), and 5 parts of polyvinyl alcohol (PVA1000).

[0105] Comparative Example 3

[0106] The difference between Comparative Example 3 and Example 1 is that the alumina in Comparative Example 3 is a single first calcined α-alumina.

[0107] A corundum crucible comprises the following raw materials in parts by weight: 95 parts of aluminum oxide, 5 parts of calcium carbonate, 1 part of dolomite, 5 parts of kaolin, 1 part of zirconium oxide, 5 parts of zirconium silicate, 1 part of zircon, 5 parts of silicon micropowder, 1 part of quartz powder, 5 parts of yttrium oxide, 1 part of lanthanum oxide, 5 parts of polyvinyl pyrrolidone (K90), and 5 parts of polyvinyl alcohol (PVA1000).

[0108] The alumina includes first calcined α-alumina. The preparation method of the first calcined α-alumina is: calcining the α-alumina at 1260° C. for 4 hours and grinding it to an average particle size of 1 μm.

[0109] Comparative Example 4

[0110] The difference between Comparative Example 4 and Example 1 is that the alumina in Comparative Example 4 is a single second calcined α-alumina.

[0111] A corundum crucible comprises the following raw materials in parts by weight: 95 parts of aluminum oxide, 5 parts of calcium carbonate, 1 part of dolomite, 5 parts of kaolin, 1 part of zirconium oxide, 5 parts of zirconium silicate, 1 part of zircon, 5 parts of silicon micropowder, 1 part of quartz powder, 5 parts of yttrium oxide, 1 part of lanthanum oxide, 5 parts of polyvinyl pyrrolidone (K90), and 5 parts of polyvinyl alcohol (PVA1000).

[0112] The alumina includes a second calcined α-alumina. The preparation method of the second calcined α-alumina is as follows: calcining the α-alumina at 1450° C. for 4 hours and grinding the α-alumina to an average particle size of 2 μm.

[0113] Comparative Example 5

[0114] Comparative Example 5 is different from Example 1 in that the mass ratio of the first calcined α-alumina and the second calcined α-alumina in Comparative Example 5 is different.

[0115] A corundum crucible comprises the following raw materials in parts by weight: 95 parts of aluminum oxide, 5 parts of calcium carbonate, 1 part of dolomite, 5 parts of kaolin, 1 part of zirconium oxide, 5 parts of zirconium silicate, 1 part of zircon, 5 parts of silicon micropowder, 1 part of quartz powder, 5 parts of yttrium oxide, 1 part of lanthanum oxide, 5 parts of polyvinyl pyrrolidone (K90), and 5 parts of polyvinyl alcohol (PVA1000).

[0116] The alumina includes a first calcined α-alumina and a second calcined α-alumina; the mass ratio of the first calcined α-alumina to the second calcined α-alumina is 1:0.2;

[0117] The preparation method of the first calcined α-alumina is: calcining the α-alumina at 1260° C. for 4 hours and grinding it to an average particle size of 1 μm.

[0118] The second calcined α-alumina preparation method is: calcining the α-alumina at 1450° C. for 4 hours and grinding it to an average particle size of 2 μm.

[0119] Comparative Example 6

[0120] The difference between Comparative Example 6 and Example 1 is that the mass ratio of the first calcined α-alumina and the second calcined α-alumina in Comparative Example 6 is different.

[0121] A corundum crucible comprises the following raw materials in parts by weight: 95 parts of aluminum oxide, 5 parts of calcium carbonate, 1 part of dolomite, 5 parts of kaolin, 1 part of zirconium oxide, 5 parts of zirconium silicate, 1 part of zircon, 5 parts of silicon micropowder, 1 part of quartz powder, 5 parts of yttrium oxide, 1 part of lanthanum oxide, 5 parts of polyvinyl pyrrolidone (K90), and 5 parts of polyvinyl alcohol (PVA1000).

[0122] The alumina includes a first calcined α-alumina and a second calcined α-alumina; the mass ratio of the first calcined α-alumina to the second calcined α-alumina is 1:4;

[0123] The preparation method of the first calcined α-alumina is: calcining the α-alumina at 1260° C. for 4 hours and grinding it to an average particle size of 1 μm.

[0124] The second calcined α-alumina preparation method is: calcining the α-alumina at 1450° C. for 4 hours and grinding it to an average particle size of 2 μm.

[0125] Comparative Example 7

[0126] The difference between Comparative Example 7 and Example 1 is that the sintering steps are different, and the other aspects are the same.

[0127] The sintering is specifically as follows: firstly, the temperature is increased to 900°C at a rate of 3°C / min, then the temperature is increased to 1300°C at a rate of 2°C / min, then the temperature is kept at 1300°C for 3h, then the temperature is decreased to 900°C at a rate of 3°C / min, then the temperature is decreased to 300°C at a rate of 2°C / min, and finally the temperature is naturally cooled to room temperature.

[0128] Comparative Example 8

[0129] The difference between Comparative Example 8 and Example 1 is that the sintering steps are different, and the other aspects are the same.

[0130] The sintering is specifically as follows: firstly, the temperature is increased to 900°C at a rate of 3°C / min, then the temperature is increased to 1600°C at a rate of 2°C / min, then the temperature is kept at 1600°C for 3h, then the temperature is decreased to 900°C at a rate of 3°C / min, then the temperature is decreased to 300°C at a rate of 2°C / min, and finally the temperature is naturally cooled to room temperature.

[0131] Test Case

[0132] Flexural strength: GB / T 3001 refractory material room temperature flexural strength test method is adopted.

[0133] Shrinkage rate: Use the dimensional method to measure the shrinkage rate; first measure the size of the inner frame of the mold, then measure the size of the green body after demolding and drying, and finally measure the size after sintering to calculate the shrinkage rate.

[0134] Table 1

[0135]

[0136]

[0137] It can be seen from Table 1 that the corundum crucible of the present invention has high strength and a small sintering yield, and has a wide range of application prospects.

[0138] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A corundum crucible, characterized in that: The invention comprises the following raw materials in parts by weight: 95-99 parts of aluminum oxide, 1-5 parts of calcium carbonate, 1-5 parts of dolomite, 1-5 parts of kaolin, 1-5 parts of zirconium oxide, 1-5 parts of zirconium silicate, 1-5 parts of zircon, 1-5 parts of silicon micropowder, 1-5 parts of quartz powder, 1-5 parts of yttrium oxide, 1-5 parts of lanthanum oxide and 2-10 parts of additives.

2. The corundum crucible according to claim 1, characterized in that: The alumina includes a first calcined α-alumina and a second calcined α-alumina; the mass ratio of the first calcined α-alumina to the second calcined α-alumina is 1:(0.5-2); The first calcined α-alumina is obtained by calcining α-alumina at 1250-1280° C. The second calcined α-alumina is obtained by calcining α-alumina at 1420-1450°C.

3. The corundum crucible according to claim 2, characterized in that: The average particle size of the first calcined α-alumina is 0.5-1 μm; the average particle size of the second calcined α-alumina is 2-4 μm.

4. The corundum crucible according to claim 1, characterized in that: The particle size of the calcium carbonate is ≥1000 mesh; The particle size of the dolomite is ≥1000 mesh; The particle size of the kaolin is ≥1000 mesh; The particle size of the zirconium silicate is ≥1000 mesh; The particle size of the zircon is ≤800 mesh.

5. The corundum crucible according to claim 1, characterized in that: The particle size of the calcium carbonate is 1000-2000 mesh; The particle size of the dolomite is 1000-2000 mesh; The particle size of the kaolin is 1000-2000 mesh; The particle size of the zirconium silicate is 1000-2000 mesh; The particle size of the zircon is 400-800 meshes.

6. The corundum crucible according to claim 1, characterized in that: The average particle size of the zirconium oxide is ≤5 μm; The average particle size of the silicon powder is ≤5 μm; The average particle size of the quartz powder is ≤5 μm; The average particle size of the lanthanum oxide is ≤5 μm.

7. The corundum crucible according to claim 1, characterized in that: The average particle size of the zirconium oxide is 1 to 5 μm; The average particle size of the silicon powder is 1 to 5 μm; The average particle size of the quartz powder is 1 to 5 μm; The average particle size of the lanthanum oxide is 1 to 5 μm.

8. The corundum crucible according to claim 1, characterized in that: The auxiliary agent includes at least one of ammonium polyacrylate, polyvinyl alcohol and polyvinyl pyrrolidone.

9. The method for preparing a corundum crucible according to any one of claims 1 to 8, characterized in that: The following steps are involved: Weigh the raw materials according to the proportion, mix them evenly, add water to prepare a slurry with a solid content of 55-65wt%; ball mill until the D90 of the slurry is ≤8μm; The slurry is placed in a gypsum mold, and the gypsum mold is allowed to absorb the slurry; after the adsorption thickness of the gypsum mold reaches a target value, it is dried and sintered to obtain a corundum crucible.

10. The method for preparing a corundum crucible according to claim 9, characterized in that: The sintering is specifically as follows: First, heat up to 880-920°C at a rate of 2.5-3°C / min, then heat up to 1450-1550°C at a rate of 1-2°C / min, then keep at 1450-1550°C for 2-5h, then cool down to 880-920°C at a rate of 2.5-3°C / min, then cool down to 280-320°C at a rate of 1-2°C / min, and finally cool naturally to room temperature.